2010
DOI: 10.1096/fj.10-175349
|View full text |Cite
|
Sign up to set email alerts
|

WNT4 is a key regulator of normal postnatal uterine development and progesterone signaling during embryo implantation and decidualization in the mouse

Abstract: WNT4, a member of the Wnt family of ligands, is critical for the development of the female reproductive tract. Analysis of Wnt4 expression in the adult uterus during pregnancy indicates that it may play a role in the regulation of endometrial stromal cell proliferation, survival, and differentiation, which is required to support the developing embryo. To investigate the role of Wnt4 in adult uterine physiology, conditional ablation of Wnt4 using the PR(cre) mouse model was accomplished. Ablation of Wnt4 render… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
228
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(240 citation statements)
references
References 49 publications
11
228
0
1
Order By: Relevance
“…We also found that downstream of LPA 3 , Bmp2/Wnt4 signaling (Table 2 and Fig 4A) was activated. Bmp2 and Wnt4 are well‐known decidual factors acting downstream of HB‐EGF signaling (Paria et al , 2001; Lee et al , 2007; Franco et al , 2011; Li et al , 2013; Large et al , 2014). Interestingly, a significant negative correlation of gene expression profiles was observed between T13‐injected uteri and uteri null for either Egfr (a target of HB‐EGF), Bmp2, and Wnt4 (Large et al , 2014; Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that downstream of LPA 3 , Bmp2/Wnt4 signaling (Table 2 and Fig 4A) was activated. Bmp2 and Wnt4 are well‐known decidual factors acting downstream of HB‐EGF signaling (Paria et al , 2001; Lee et al , 2007; Franco et al , 2011; Li et al , 2013; Large et al , 2014). Interestingly, a significant negative correlation of gene expression profiles was observed between T13‐injected uteri and uteri null for either Egfr (a target of HB‐EGF), Bmp2, and Wnt4 (Large et al , 2014; Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Maternal factors such as heparin‐binding epidermal growth factor (HB‐EGF) and cyclooxygenase‐2 (COX‐2) are induced in the epithelium surrounding the embryos (embryo‐epithelial interaction) and then act on the stroma to induce the expression of bone morphogenic protein 2 (Bmp2) and wingless‐related MMTV integration site 4 (Wnt4) in stroma (epithelial–stromal interaction; Lim et al , 1997; Paria et al , 2001; Song et al , 2002; Wang et al , 2004; Xie et al , 2007; Large et al , 2014). Mice in which these maternal factors (HB‐EGF, COX‐2, Bmp2, and Wnt4) are knocked out showed obvious defects in decidual reactions (Lim et al , 1997; Wang et al , 2004; Lee et al , 2007; Xie et al , 2007; Franco et al , 2011; Li et al , 2013; Large et al , 2014). Based on these observations, it has been proposed that some factor(s) are present in the embryo‐epithelial boundary and induce the expression of HB‐EGF and COX‐2 in the epithelium, which in turn facilitate the following decidual reactions through up‐regulation of Bmp2 and Wnt4 (Paria et al , 2001; Cha et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear localization of forkhead box protein O1 (FOXO1), a transcription factor and a promoter of apoptosis is controlled by Wnt4 in adult mouse uterus. When Wnt4 was conditionally ablated, FOXO1 was determined to be expressed in the nucleus, suggesting that FOXO1 actively promoted the transcription of pro-apoptotic genes [32].…”
Section: Wnt Signaling In Uterine Receptivitymentioning
confidence: 99%
“…Wnt4 was also shown to be associated with development of endometrial glands in mice [41]. In Wnt4 ablated mouse models, the amount of endometrial glands were reduced compared to control mice [32], hypertrophy and pseudostratification of the LE occured which may account for the difficulty of embryo invasion [41]. Wnt4 was associated with a number of transcription factors such as FOXO1 and KLF9 in mouse uterus [32].…”
Section: Wnt Signaling In Uterine Receptivitymentioning
confidence: 99%
See 1 more Smart Citation